The Influence of Using Digital Games on the Games to Learn English Website on Elementary School Students' English Vocabulary Mastery - Siti Hanisa Mulyani; Nadia Tiara Antik Sari; Wina Mustikaati (Yayasan Vifada Cendikia Indonesia, 2026)
Vocabulary mastery is an essential component of learning English, yet elementary school students often face challenges in lexical competency. This study aims to evaluate how digital games on the Games to Learn English website affect and improve fifth-grade students' understanding of Comparative Adjectives vocabulary. A pre-experimental method with a One-Group Pretest-Posttest Design was employed, involving 32 fifth-grade students at SDN 2 Mulyamekar Purwakarta. Data were collected through observation sheets and assessments measuring vocabulary indicators: Pronunciation, Meaning Recognition, Spelling Accuracy, and Contextual Usage. The findings showed that the mean score increased from 67.44 in the pre-test to 72.50 in the post-test. The Wilcoxon Signed Ranks Test confirmed a significant impact (Asymp. Sig. 0.042 < 0.05). Although the N-Gain score averaged 0.0590 (5.9%), placing it in the low category due to high baseline pre-test scores, the website remains an effective learning alternative. This study implies that digital game-based learning can enhance vocabulary mastery, though future research should consider extending treatment duration and adjusting digital media to better meet students' affective needs in the classroom.